DESAIN PENGELOLAAN DAN PEMANTAUAN DAMPAK LINGKUNGAN TERHADAP REKONSTRUKSI GEDUNG KANTOR GUBERNUR SULAWESI BARAT - Satriawan, Andi Muh. Dayri; Desi, Natsar; Indrayani, Poppy (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
As a form of service to the community, Pj. The Governor of West Sulawesi plans to rehabilitate and reconstruct the West Sulawesi Governor's Office Building. As a result of these activities it has negative impacts in the form of reduced air quality, increased noise, increased surface water runoff, health problems for local employees, and piles of domestic waste resulting from construction activities. In order to overcome the negative impacts that occur and develop the positive impacts of management efforts, it is necessary to carry out environmental impact studies that occur during the pre-construction, construction and operation stages. The purpose of this study is to obtain the results of an managing of environmental impact studies and countermeasures in minimizing the impacts that occur during the pre-construction, construction and operation stages. The method used in this research is the observation method and the scoping method to determine the impact and good handling of the environment. This study uses primary data in the form of field surveys, interviews, and is supported by secondary data. The result of this research is to know the initial environmental baseline conditions at the research location and obtain an analysis of the environmental impacts that occur and ways to minimize the impact with good handling in order to create an environmentally friendly construction.